Effects of nitrogen addition on SOC in alpine grasslands of the Qinghai-Tibetan Plateau and adjacent mountain regions: a meta-analysis - Ye, Yanhui; Wu, Zheng; Zhang, Shaobing; Tong, Lingchen; Huang, Wenqiang; Cui, Zhipan; Han, Yanying (Frontiers in Environmental Science, 2025)
AimsNitrogen (N) deposition has emerged as a major driver of ecological change in alpine grasslands of the Qinghai-Tibetan Plateau under global climate change. To predict the ecological consequences of increasing nitrogen deposition, nitrogen addition experiments have been widely employed as a key methodological approach to simulate this process. However, the effects of nitrogen addition—considering its rate, duration, and form—on carbon (C) dynamics in these ecosystems remain inconsistent across studies. Understanding these effects is critical for predicting global carbon stocks and guiding sustainable grassland management.MethodsWe conducted a meta-analysis of 57 peer-reviewed studies (794 observations) to quantify the response of alpine grassland C dynamics to N addition.ResultsN addition significantly increased plant-derived carbon inputs, increasing aboveground biomass by 42.7%, belowground biomass by 16.2%, and dissolved organic carbon (DOC) by 10.7%. The soil organic carbon (SOC) content increased by 3.6% overall. Conversely, soil respiration decreased by 5.1%, whereas the microbial respiration rate increased by 21.9%. The addition of nitrogen decreased the soil pH by 0.20 units and the soil C/N ratio by 1.7%. The soil ammonium (NH4+) and nitrate (NO3-) contents decreased by 20.1% and 52.1%, respectively. The microbial biomass nitrogen (MBN) increased by 14.5%, whereas the microbial biomass carbon (MBC) decreased by 2.8%. The soil fungal-to-bacterial ratio (F/B) decreased by 31.0%.ConclusionThese results indicate that shifts in microbial community structure drive SOC dynamics in alpine grasslands. Short-term N addition (≤5 years; ≤30 kg N ha-1 yr-1) enhances SOC through increased plant biomass and microbial C sequestration. However, long-term additions promote C loss via soil acidification and a critical shift in the microbial community, notably a decreased fungal-to-bacterial ratio. To sustain alpine ecosystem function, N addition rates should not exceed 10 kg N ha-1 yr-1. Future research should prioritize interactions between N deposition status and soil acidification/microbial function in high-altitude regions.